2011
DOI: 10.1074/jbc.m111.235366
|View full text |Cite
|
Sign up to set email alerts
|

Munc18-1 and Munc18-2 Proteins Modulate β-Cell Ca2+ Sensitivity and Kinetics of Insulin Exocytosis Differently

Abstract: Fast neurotransmission and slower hormone release share the same core fusion machinery consisting of SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins. In evoked neurotransmission, interactions between SNAREs and the Munc18-1 protein, a member of the Sec1/Munc18 (SM) protein family, are essential for exocytosis, whereas other SM proteins are dispensable. To address if the exclusivity of Munc18-1 demonstrated in neuroexocytosis also applied to fast insulin secretion, we char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…This is of importance, as first-phase GSIS is much reduced in patients with type 2 diabetes, and this has been attributed in part to greatly reduced islet SYN-1A levels [23], along with reduction of cognate SNAREs (SNAP25 and VAMP2) and the Sec1/Munc18-like protein (SM) Munc18a. SYN-3 was shown in pancreatic acinar cells to preferentially form complexes with VAMP8 [20] and Munc18b [38,39], which are also present in beta cells [40][41][42]. We recently reported, employing the Vamp8-knockout mice [43], that VAMP8 also mediated the recruitment and fusion of newcomer SGs, and was the putative cognate v-SNARE that binds SYN-3.…”
Section: Discussionmentioning
confidence: 99%
“…This is of importance, as first-phase GSIS is much reduced in patients with type 2 diabetes, and this has been attributed in part to greatly reduced islet SYN-1A levels [23], along with reduction of cognate SNAREs (SNAP25 and VAMP2) and the Sec1/Munc18-like protein (SM) Munc18a. SYN-3 was shown in pancreatic acinar cells to preferentially form complexes with VAMP8 [20] and Munc18b [38,39], which are also present in beta cells [40][41][42]. We recently reported, employing the Vamp8-knockout mice [43], that VAMP8 also mediated the recruitment and fusion of newcomer SGs, and was the putative cognate v-SNARE that binds SYN-3.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions of another member of the STXBP family, STXBP3, with syntaxin 4 have been shown to influence second-phase GSIS, but the precise exocytotic event has not been elucidated [18]. A recent paper on STXBP2 reported that overexpression of this member of the STXBP family in beta cells increased calcium sensitivity to evoke a larger exocytotic response [19], implicating that this protein modulates a distinct set of SNARE proteins. Much further work will be required to elucidate the identities and functions of these as yet undefined membrane fusion SNARE molecules, the accessory proteins that modulate the assembly and disassembly of these SNARE complexes and the precise exocytotic events shown in Fig.…”
Section: -Dmentioning
confidence: 99%
“…ii) Certain SM proteins interact in other ways with the syntaxin protein family; the SM proteins combine with the N terminal sequence of the conserved syntaxin protein, which is termed the open state. This interaction is more common than the aforementioned interaction (6,25). iii) The direct combination of SM proteins and the SNARE complex.…”
Section: Other Proteins Participate In Insulin Secretory Granules Exomentioning
confidence: 99%